1989
DOI: 10.1007/bf00253629
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characteristics of neurons in neocortical expiant cultures

Abstract: We examined the electrophysiological and morphological properties of neocortical neurons maintained in explant cultures prepared from the parietal cortex of newborn Sprague-Dawley rats. After 3-6 weeks in vitro, cultures showed regional differences in cellular density reminiscent of cortical layering, and an abundance of axonal processes. Pyramidal-shaped neurons with spinous dendrites were the dominant elements revealed by Lucifer yellow injections. Intracellular recordings revealed that many electrophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These neurons showed spike firing properties similar to those in regular spiking neurons (McCormick et al . 1985; Wolfson et al . 1989).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons showed spike firing properties similar to those in regular spiking neurons (McCormick et al . 1985; Wolfson et al . 1989).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we analysed neurons with stable (> 1 h) resting membrane potentials deeper than ±50 mV. These neurons showed spike ®ring properties similar to those in regular spiking neurons (McCormick et al, 1985;Wolfson et al, 1989). We found that electrical stimulation of the partner explant rarely evoked postsynaptic potentials (PSPs) in the VC neurons before 7 days in vitro (7 DIV).…”
Section: General Featuresmentioning
confidence: 87%
“…Scale bar = 2 pm. control cultures showed a low level of spontaneous activity, similar to that seen in other organotypic slice culture systems (Wolfson et al, 1989). In order to determine whether the PTX effects observed in this study were attributable to elevated levels of electrophysiological activity and to determine the effect of low spontaneous activity on spine density, a series of cultures were grown in the presence of both PTX and TTX.…”
Section: Effects Of Chronic Pharmacological Manipulation On Cortical mentioning
confidence: 90%
“…To solve equation 2.7, four parameters need to be specified: t 0 , τ , V th , and C. Parameter choices are based on physiological values observed in cortical pyramidal cells of the rat and the cat, summarized and derived in Bugmann (1991). The input injection current, I inj , varies over a realistic range of current injection: [1I rh , 13I rh ] amperes, with threshold potential, V th = 15 mV (see Wolfson et al 1989). V th lies between the axon hillock threshold and the soma fast sodium conductance threshold (Schwindt and Crill 1982).…”
Section: Parameter Choicesmentioning
confidence: 99%